EMPOWERMENT OF THE DHUAFA', FAKIR AND POOR AL-QUR'AN PERSPECTIVE - Ridho, Abdul Rasyid; Muhammad Taufiq (UIN Mataram, 2023)
Abstract: The existence of the dhu'afa, fakir and poor is a phenomenon that almost occurs in all developing countries. The inability of some people to fulfill their needs is the cause of poverty. This condition is also the cause of the decline in the quality of human resources, productivity and low income. So that with this low income, it affects the difficulty of getting access to education, health, and good nutrition. Economic development since independence has significantly reduced the number of poor people in Indonesia. However, the ongoing monetary crisis became an economic crisis that resulted in an economic downturn that increased the number and proportion of poor people to almost half of Indonesia's population. Therefore, whatever the cause of poverty, it remains a major problem and requires attention and concrete action from both rescue, empowerment and facilitative programs from the government. This article tries to provide steps and solutions to empower the dhu'afa, the poor and the poor from the perspective of the Qur'an. Keywords: Poverty, Empowerment, Qur'anic Perspective